Journal of Wood Science Official Journal of the Japan Wood Research Society - Umemura, Kenji; Watanabe, Takashi; Fujii, Yoshihisa; Fujii, Yoshihisa; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer.)
The Journal of Wood Science is the official journal of the Japan Wood Research Society. This journal provides an international forum for the exchange of knowledge and the discussion of current issues in wood and its utilization. The journal publishes original articles on basic and applied research dealing with the science, technology, and engineering of wood, wood components, wood and wood-based products, and wood constructions. Articles concerned with pulp and paper, fiber resources from non-woody plants, wood-inhabiting insects and fungi, wood biomass, and environmental and ecological issues in forest products are also included. In addition to original articles, the journal publishes review articles on selected topics concerning wood science and related fields. The editors welcome the submission of manuscripts from any country.
Keywords: Biogeography; Materials science; Materials$1 (BAnalysis.s; Biogeosciences; Materials Science; Characterization and Analytical Technique